2021
DOI: 10.1186/s12935-021-02150-0
|View full text |Cite
|
Sign up to set email alerts
|

Cinobufagin-induced DNA damage response activates G2/M checkpoint and apoptosis to cause selective cytotoxicity in cancer cells

Abstract: Background Processed extracts from toad skin and parotoid gland have long been used to treat various illnesses including cancer in many Asian countries. Recent studies have uncovered a family of bufadienolides as the responsible pharmacological compounds, and the two major molecules, cinobufagin and bufalin, have been shown to possess robust antitumor activity; however, the underlying mechanisms remain poorly understood. Methods Intracellular react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…In non-small cell lung cancer, cinobufagin could suppress proliferation, migration, and invasion of cancer cells by inhibiting the expression of G9a[ 27 ]. By interfering with the cell cycle, cinobufagin also inhibits the survival of cancer cells and promotes apoptosis[ 28 ]. Moreover, many other anti-tumor pathways are involved, such as the Notch signaling pathway[ 29 ], AURKA/mTOR/eIF4E axis[ 30 ], c-Myc pathway[ 31 ], and ROS/JNK/p38 signaling pathway[ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In non-small cell lung cancer, cinobufagin could suppress proliferation, migration, and invasion of cancer cells by inhibiting the expression of G9a[ 27 ]. By interfering with the cell cycle, cinobufagin also inhibits the survival of cancer cells and promotes apoptosis[ 28 ]. Moreover, many other anti-tumor pathways are involved, such as the Notch signaling pathway[ 29 ], AURKA/mTOR/eIF4E axis[ 30 ], c-Myc pathway[ 31 ], and ROS/JNK/p38 signaling pathway[ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, cinobufagin was shown to inhibit the growth of cancer cells but did not reduce the viability of noncancerous cells such as human L-O2 liver and NCM460 colon epithelial cell lines (Dai et al, 2018b;Niu et al, 2021), demonstrating that cinobufagin is selectively toxic to cancerous cells. Our study showed that the cytotoxicity of cinobufagin to HepG2 cells is concentrationand time-dependent, high concentration and long exposure generated more cytotoxicity, suggesting that cinobufagin might interact with HepG2 directly and indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Given the aforementioned panel of markers, the radioprotective activity of each modulator was investigated. First, cinobufagin was selected as a candidate radioprotector as it may activate the ATM-CHK2 signaling pathway, which promotes DNA repair ( 32 ). Several studies have demonstrated that cinobufagin exerts anti-inflammatory ( 33 ), anti-bacterial ( 34 ), antitumor ( 35 , 36 ) and immune-enhancing effects ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%